Potential Benefits of Metaverse Concept Implementation in English for Tourism Course: A Case Study in Indonesian Higher Education Contexts - Pujasari, Ratu Sarah; Fatimah, Asri Siti; Sri, Melisa; Sulastri, Fera (Universitas Negeri Makassar, 2024)
This study described the potential benefits of implementation of the Metaverse concept in English for Tourism course revealing views from the students’ perception. This research used a qualitative descriptive case study to investigate the phenomenon of the use of metaverse at higher educational levels in the Indonesia context. During data collection, an interview was conducted to gather the student's perspective on the notion of metaverse in English for the Tourism course, and the document served as secondary data as the artifact utilized in the subject's classroom activity. Thematic analysis was used to interpret the data. Based on the findings, there are two benefits of implementing metaverse concepts in English for tourism course. The study implemented two metaverse platforms namely spatial.io and readyplayerme. The study showed that the students showed their positive perception towards the use of these platforms. Integrating a virtual environment in a metaverse concept gives prospects for immersive and interactive learning enhancing the students’ learning engagement. In addition, since the students need to have the capability to use the platform, their digital literacy was also developed.